Diseño conceptual para la mejora del proceso en la producción de moringol en la empresa Juleps Pharma LTDA. Laboratorios (2017)
For the development of the present work of degree, it was proposed the realization of a conceptual design for the production process of Moringol in the company Juleps Pharma Laboratories Ltda., on the basis of the improvement of the method of production of the extract of Moringa oleifera Lam, the company is currently performing the removal by means of a mixture hydro-alcoholic, which, although it is a method that helps the performance of the extract, is an extensive process of obtaining and for the quantities that are used ( 50- 60 ml per product), they tend to take up a large amount of space in the storage and a large amount of raw material for the obtaining of the extract, this Makes the costs of production increase, in addition to all the above factors such an astringent taste in the finished product and therefore sets out the objective of the project.